Pengelolaan Badan Usaha Milik Desa (Bum Desa) Bumi Patalo di Desa - Agus Susanto; saru reza (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2018)
This type of research is field research with a qualitative approach. Data collection methods include observation, interviews and documentation. The results of the study show that 1) the management system has not been implemented properly because the indicators used such as planning, organizing, monitoring, directing have not been carried out optimally 2) Factors that influence the Management of Village Owned Enterprises (BUM Desa) Patalo Bumi in Farmers Village there are two, namely the lack of community participation and human resources.